2000
DOI: 10.1128/jb.182.14.3920-3923.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Promoter Region Binding Protein and DNA Gyrase Regulate Anaerobic Transcription of nifLA in Enterobacter cloacae

Abstract: Our work provides evidence that a sequence characteristic of FNR binding sites, when interacted with by a trans-acting factor, activates anaerobic transcription of the nifLA operon in Enterobacter cloacae. DNA gyrase activity has been found to be important for the anaerobic transcription of the nifLA promoter. Our results suggest that anaerobic regulation of the nifLA operon is mediated through the control of the promoter region-binding trans-acting factor at the transcriptional level, while DNA supercoiling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Complementation by the wild-type fnr sequence restored all abolished phenotypes. Based on GenBank entries, our nucleotide sequence analysis is the first to identify the fnr gene in Enterobacter; however, previous studies have reported an FNR-like protein in E. cloacae associated with the anaerobic transcription of 1-aminocyclopropane-1-carboxylate deaminase and the nifLA operon (9,12,23). Our data indicate that the fnr gene in E. cloacae SLD1a-1 is essential for Se(VI) reduction and is linked to anaerobic electron transfer processes.…”
Section: Discussionmentioning
confidence: 87%
“…Complementation by the wild-type fnr sequence restored all abolished phenotypes. Based on GenBank entries, our nucleotide sequence analysis is the first to identify the fnr gene in Enterobacter; however, previous studies have reported an FNR-like protein in E. cloacae associated with the anaerobic transcription of 1-aminocyclopropane-1-carboxylate deaminase and the nifLA operon (9,12,23). Our data indicate that the fnr gene in E. cloacae SLD1a-1 is essential for Se(VI) reduction and is linked to anaerobic electron transfer processes.…”
Section: Discussionmentioning
confidence: 87%
“…Nalidixic acid is an inhibitor of DNA gyrase, which can unwind DNA supercoiling in a replication fork [3]. DNA replication blocking by nalidixic acid treatment caused Microcystis cells to inhibit the cell division and repress of ftsZ expression; however, it is known that DNA gyrase also selectively regulates the transcription of some genes [18]. We therefore used a different method of blocking chromosome replication, using hydroxyurea, which is an inhibitor of ribonucleotide reductase [2].…”
Section: Discussionmentioning
confidence: 99%
“…The transcription of genes involved in nitrogen fixation has been shown to be sensitive to the supercoiling state of DNA in several different bacteria including Rhodopseudomonas capsulata, Klebsiella pneumoniae, Enterobacter cloacae, Sinorhizobium meliloti and the cyanobacterium Gloeothece (Nageli) sp. ATCC 27152 (Kranz and Haselkorn, 1986;Dimri and Das, 1988;Page and Gallon, 1992;Hu et al, 2000;Liu et al, 2005). Supercoiling of DNA is a topological change that can be assayed by changes in fluorescence using fluorescent DNA stains (Lebaron and Joux, 1994;Prosperi et al, 1994).…”
Section: Introductionmentioning
confidence: 99%